Ответы и объяснения

  • Minsk00
  • почетный грамотей
2014-01-19T09:27:41+04:00
A) (1/4)^(1+ 0,5log1/2(14))
(1/4)^(1+ 0,5log1/2(14)) = (1/2²)^(1+ 0,5log1/2(14)) = (2^(-2))^(1+ 0,5log1/2(14)) =
=(2^(-2))*(2^(-2))^(0,5log2^(-1)(14)) = (1/4)*(2^(-2))^(-0,5log2(14)) =
= (1/4)*(2^((-2)*(-0,5log2(14))) = (1/4)*(2^log2(14)) =(1/4)*14 =14/4 =7/2 =3,5
b) 25^(1 - 0,5log5(11)) = (5^(2))^(1 - 0,5log5(11)) = (5^(2))*(5^(2))^(-0,5log5(11)) =
=25*5^(2*(-0,5log5(11))) = 25*5^(-log5(11)) = 25*5^log5(1/11) = 25*(1/11) =25/11 =2 3/11
Ответ: a) 3,5; b) 25/11/